Friends in the Mail / by Fran Manushkin ; illustrated by Laura Zarrin - Manushkin, Fran; Zarrin, Laura (North Mankato, Minnesota : Picture Window Books, 2020)
On a trip to the post office to mail a present to her grandfather, Katie learns all about how the mail works.
Keywords: Woo, Katie -- (Fictitious character) -- Juvenile fiction; Readers (Primary); Chinese American families -- Juvenile fiction; Postal service -- Juvenile fiction